Educação e extensão rurais para a agricultura familiar através do Programa “Campo - Saberes da Terra" no município de Bragança: agroecologia e sustentabilidade para o desenvolvimento rural e de jovens do campo - QUEIROZ, Jardel Costa (Universidade Federal do Pará, 2019)
This thesis comprises a case study of the experiences of the government implemented “Campo – Saberes da Terra” in the municipality of Bragança, located in the northeastern state of Pará. The study of this experiment was carried out by qualitative research over a period one year and four months having as object of study rural education and rural extension for local development through the identity of the family farm worker youth of the field to the paradigm of agroecology. This work was developed through a participatory social effort dialogic which presents results of a research qualified by training and experience experienced by social actors in their reality they developed and transformed into new living conditions. This research goes against the relentless pursuit of social and rural development away from the rhetoric of traditional research